Dampak Dari Kesadaran Pajak Dan Hukuman Pajak Terhadap Tingkat Kepatuhan Pemilik Kendaraan Bermotor Dengan Pengetahuan Pajak Sebagai Faktor Yang Mempengaruhi - Merida Merida; Khrisna Anggun Yuliana; Muh Rays (STIE Amkop Makassar, 2025)
Many taxpayers think that tax obligations are a burden and threat to them, so they hesitate to pay taxes or tend to avoid paying taxes. In addition, the many acts of corruption that occur in the tax environment make people even more reluctant to pay taxes. The application of tax sanctions results in compliant taxpayers, in which case taxpayers comply because they consider severe sanctions as a penalty for unlawful acts in tax avoidance efforts. The source of data obtained in this study comes directly from taxpayers at the balaraja samsat, Tangerang district. Then the minimum sample to be used in this study is 100 Respondents. The data analysis technique used is Moderated Regressions Analysis using SPSS version 25 for windows. The results of this study indicate that taxpayer awareness has a significant effect on motor vehicle taxpayer compliance with a significant value of 0.000 <0.05. Tax sanctions have a significant effect on motor vehicle taxpayer compliance with a significant value of 0.000 <0.05. The moderating variable, namely taxation knowledge, is able to moderate the relationship between taxpayer awareness and motor vehicle taxpayer compliance which results in a significant value of 0.000 <0.05 and the moderating variable of taxation knowledge is also able to moderate the relationship between taxation sanctions and motor vehicle tax compliance which results in a significant value of 0.000 <0.05 and the moderating variable of taxation knowledge.